(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Reading acts as a separate and independent type of communicative activity, the motive of which is to satisfy the need to obtain information from different texts. In this regard, reading is widely used for aesthetic, cognitive purposes, educational, household and industrial spheres, where extracting information from a specific text through reading serves to carry out various types of activities. Reading plays an important role in the process of learning a foreign language. In existing textbooks for technical universities, insufficient attention is paid to the development of reading techniques as a type of speech activity. The need for additional methodological developments for the development of reading skills determined the relevance of the topic of our article.